Motivasi Belajar Siswa Kelas XI dalam Pembelajaran Beladiri Pencak Silat di SMK Rosma - Kurniawan Kurniawan; Bambang Ismaya; Abdul Salam Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the Learning Motivation of Class XI Students in Learning Pencak Silat at SMK Rosma. This study uses a quantitative approach. If viewed from the type of data presented, the method in this study is a survey research using a questionnaire. The sample used is purposive sampling, totaling 90 students. The results obtained with the category of "low" by 14% (13 students), "enough" by 79% (71 students), "high" by 7% (6 students), Sufficient Learning Motivation of Class XI Students in Self-Defense Learning Pencak Silat at SMK Rosma is influenced by two things; the first is the intrinsic factor of 48.72%, the second is the extrinsic factor of 51.28%.